Mechanical signature and full-field measurement of flow-induced large in-plane deformation of fibrous reinforcements in composite processing. (March 2019) - Hautefeuille, A.; Comas-Cardona, S.; Binetruy, C.
Abstract: During compression of saturated fibrous reinforcement, the flow of the liquid can, under certain conditions, generate fiber-tows washout (in-plane movement of fiber-tows) due to the strong hydrodynamically induced force on the fibrous reinforcement. The objective of the study is first to detect experimentally the onset and measure the full-field magnitude of the flow-induced in-plane deformation occurring during the compression. Secondly, a methodology is presented, aiming at defining the mechanical signature of fiber-tow washout on transverse compression tests. For this purpose, a large-scale semi-transparent test bench has been developed in order to dynamically track the in-plane motion of the fiber-tows occurring in saturated compression. Then, a nomogram is given to identify a process window of a saturated fibrous reinforcement processed by consolidation.